The Program for Self-Regulated Learning: An Empirical Study on Students-Survival Skills in Pesantren - Susanto, Susanto; Ritonga, Apri Wardana; Desrani, Ayu; Rubiyantoro, Yohan; Hude, M. Darwis (Jurnal Ilmiah Peuradeun, 2025)
Pesantren plays a significant role in developing students’ self-regulated learning (SRL) skills, which are reflected in their ability to set learning goals and manage their cognition, motivation, and behavior. However, previous studies did not explore SRL skills among students in pesantren, particularly in those with three secondary education units: MA (Madrasah Aliyah), SMA (Senior High School), and SMK (Vocational School). This study aimed to reveal the average SRL skills of students and their indicators in supporting survival skills (SS) in pesantren. Using a positivistic paradigm and a quantitative approach through survey methods, this research was conducted at Pesantren As-Syifa Al-Khoeriyyah Subang, West Java, Indonesia, involving 99 students from MA, SMA, and SMK levels as samples. Data were collected through a questionnaire consisting of 30 questions and analyzed using ANOVA. The results showed that the average SRL skill scores for MA students were 55.48, for SMA students 60.12, and for SMK students 57.72, with an overall average score of 57.77. The ANOVA significance test value of 0.012 (< 0.05) indicates a significant difference between groups. This study also highlighted that students’ SRL skills, such as social independence, values, and behavior, were shaped through various programs implemented in the pesantren.